The rapid determination of total polyphenols content and antioxidant activity in Dendrobium officinale using near-infrared spectroscopy. Issue 23 (25th May 2016) - Ma, Longhui; Zhang, Zhimin; Zhao, Xingbing; Zhang, Sufeng; Lu, Hongmei
Abstract : NIR spectroscopy coupled with chemometric methods for rapid quantification of total polyphenols content and antioxidant activity in Dendrobium officinale . Abstract : Despite their popularity and extensive use, some herbs have not been officially recognized in most countries. The main reason is the lack of comprehensive research data and methods. In this study, a rapid approach based on near-infrared spectroscopy (NIR) was developed for the determination of total polyphenols content (TPC) and antioxidant activity (AA) in Dendrobium officinale ( D. officinale ), an important Chinese herb. Adopting the Folin–Ciocalteu (FC) assay and 2, 2-diphenyl-1-picrylhydrazyl radical (DPPH) free radical scavenging activity as the reference methods, TPC and AA in D. officinale samples ( n = 83) collected from different locations in China were analyzed. The spectra generated by NIR were pretreated with different pre-processing methods and analyzed with the partial least-square (PLS) method. To obtain a robust and predictive quantitative model, competitive adaptive reweighted sampling (CARS) was applied to screen the key variables. The correlation coefficient of prediction ( R pre 2 ) and root mean square error of prediction (RMSEP) by competitive adaptive reweighted sampling-partial least-square (CARS-PLS) were 0.8412 and 0.2905 for TPC and 0.9062 and 0.1028 for AA. The results show that the combination of NIR spectroscopy with CARS-PLS provides a rapid and precise alternative to existing chemical analysis for the determination of TPC and AA in D. officinale .